(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The use of zar zaman poetry in the school literary education system lays certain foundations for itsteaching. Therefore, the aim of this study was to identify and scientifically substantiate methodological approachesto studying works of that time by Dulat Babataiuly, Shortanbai Kanaiuly, and Murat Monkeuly. The methodologyemployed systemic, historical-literary, axiological, competency-based, and hermeneutic approaches. The studyutilized an analysis of scientific literature, an analysis of the contents of school textbooks (grades 5, 7, and 8), as wellas comparison and interpretation. The object of the study was zar zaman poetry in the content of school literaryeducation within the subject «Kazakh Literature», and the subject of the study was its theoretical and methodologicalfoundations of teaching.The study revealed the educational potential of zar zaman poetry and the values it embodies, as well as adynamic increase in the complexity of its study across grades and methodological continuity from the reproductive tothe analytical and interpretive-research levels. It was established that the axiological concepts of adamdyq, zaman, andzher/el form the basis of students' historical consciousness and national worldview. Their scientific significancesubstantiates the theoretical and provides methodological foundations of teaching zar zaman poetry. Their practicalsignificance suggests the use of the results in improving Kazakh literature teaching methods.